Using MODE to explore the spatial and temporal characteristics of cloud cover forecasts from high‐resolution NWP models. (22nd May 2013) - Mittermaier, M. P.; Bullock, R.
ABSTRACT Cloud forecasts pose a particularly difficult challenge to verification through the three‐dimensional structure of cloud. Two‐dimensional total cloud forecasts from one convection‐permitting and one near‐convection‐resolving Numerical Weather Prediction (NWP) model are compared to a cloud analysis using the Method for Object‐based Diagnostic Evaluation (MODE) and MODE Time Domain (TD) which is currently being developed to also consider the time dimension. This study attempts to quantify the spatial and temporal evolution of specifically persistent (static) and systematic cloud scenarios where the cloud boundaries change only slowly. These scenarios can lead to significant cloud and temperature errors if the locations of these boundaries are not well forecast. MODE and MODE TD are used to identify and compare the number of cloud free objects, their evolution over time in terms of area or volume. The results show that including the time dimension provides a different perspective to the assessment, but that the choice of method‐specific parameters is critical for enabling the matching of time objects. Crucially, model‐relative behaviour can be isolated, and the specific characteristics of the cloud analyses are also quantifiable, and need to be accounted for when interpreting results. Copyright © 2013 Royal Meteorological Society and British Crown copyright, the Met Office